Evaluation and Redesign Based on Highway Geometric Design Guidelines 2021 (Case Study of Sampakan–Singosaren Road KM 13.8, Bantul Regency) - Wibowo, Dian Eksana; Putra, Yoga Pratama; Ma'arif, Faqih (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
This study aims to : (1) evaluate the geometric design of the Sampakan–Singosaren street km 13,8 Bantul Regency based on Panduan Desain Geometrik Jalan Bina Marga 2021; (2) identify the factor considered as evaluation, (3) propose alternative design and (4) to evaluate the differences between existing geometric design and alternative geometric design. The study used trial-and-error modeling for existing, and alternative geometric using Auto cad Civil 3D Student Version and analyzed according to Bina Marga standard. Then, a comparison of the existing and alternative geometric designs is calculated based on Bina Marga Geometric Design Standard 2021. The result indicates of study that there are 2 (two) existing curves with (1) each radius range at 37 m and 30 m, respectively; (2) the horizontal sight line offset on the first curve and the second curve was 4,7 m and 0.7 m, and the driving speed of 40 km/h. Furthermore, there is some parameter that does not meet the requirements, so an alternative design is required to fulfill the requirements of Bina Marga Geometric Design Standard 2021; (3) The designed shift on the new track to ± 9 m east and ± 5 m south; (4) the radius in both curve (S-C-S) is about 44 m, (5) horizontal sight line offset on the first curve and the second curve was 8,38 m and 7,557 m. Some changes to the existing and alternative design are the larger radius, the lower super elevation, new track is more flexible, and the better JPH and horizontal sight line offset.